CHRONIC DISTAL BICEPS TENDON RUPTURE: RETROSPECTIVE REVIEW OF OUTOCOMES OF A NOVEL TECHNIQUE OF RECONSTRUCTION WITH TENDON GRAFT. Issue 9 (10th May 2013) - Goetz, T; Okada, M; Scott, A; Pike, J
Abstract : Introduction: The biceps brachii muscle is the primary forearm supinator and a secondary elbow flexor. The pathophysiology of distal tendon ruptures is still unclear. Patients with chronic rupture presenting 4–6 weeks after the original injury often due to mis-diagnosis or neglect have been, until recently treated non-operatively. The chronic case of biceps tendon rupture poses a surgical challenge due the retraction of the muscle and scarring or resorption of the tendon that may make it impossible to reattach primarily. A novel technique of reconstruction using tendon graft has been developed by the author. The study aims to measure subjective and objective outcomes of reconstruction with this technique. Methods: This is a retrospective review of nine patients (mean age 47±10) treated with tendon reconstruction an average of 17 months following injury. Patients were evaluated and graded for bicep contour, range of motion, Mayo Elbow Performance Index (MEPI) and for bilateral elbow flexion and supination torque on a Biodex System 4 Pro dynamometer. Patient reported outcome questionnaires were also collected. Results: The mean Disabilities of the Arm, Shoulder, and Hand score (DASH), American Shoulder and Elbow Society score (ASES), and Mayo Elbow Performance Index (MEPI) were 11±10, 91±10, and 88±14 respectively. Eighty of nine subjects were somewhat or very satisfied with the reconstruction. Biceps contour was 4.7 cm above the antecubital fossa on the operative side versus 3.9 cm on the nonoperative side. No statistically different strength discrepancies were noted between the operative and nonoperative sides when comparing isometric supination strength (p=0.42) and flexion strength (p=0.17), as well as peak supination torque at 90 degrees of elbow flexion (p=0.09). Discussion: Reconstruction of chronic distal biceps tendon rupture with tendon graft resulted in low patient-reported disability and high patient satisfaction. No statistically different values in isokinetic supination and elbow flexion strength were noted between operative and nonoperative sides. No loss of ROM was noted as a result of the reconstruction.